Abusive Transfer Pricing and Economic Activity - Søren Bo Nielsen; Dirk Schindler; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2014)
We demonstrate that the choice of the transfer price and its effect on intra-firm trade and investment depends on the probability of detection and thus on the measure, on which tax authorities base their audit. A policy implication of the paper is that it should be preferable to condition audits on the amount of income shifted rather than on the distortion of the transfer price proper. Another policy finding is that improving the quality of tax law might be superior to higher detection effort. The former reduces profit shifting and concealment effort, whereas the latter leads to more wasteful use of resources on concealment and has an ambiguous effect on profits shifted.
Keywords: H25; 330; transfer pricing; investment; concealment costs; economic activity